“MANUAL DE CONTROL INTERNO PARA LOS SUB-PROCESOS DE LA GERENCIA DE LA COOPERATIVA DE AHORRO Y CREDITO ECOSUR DEL CANTÓN SARAGURO DE LA PROVINCIA DE LOJA - JIMÉNEZ ABAD, GABRIEL FRANCISCO (2019)
The degree work called "INTERNAL CONTROL MANUAL FOR SUB-PROCESSES OF THE MANAGEMENT OF THE ECOSUR SAVINGS AND CREDIT COOPERATIVE OF THE SARAGURO CANTON OF THE PROVINCE OF LOJA", aims to become a management tool with the purpose of provide the human resource with rules, policies and procedures that help improve the development of their work activities efficiently and effectively and thus achieve the goals proposed by the Cooperative. To carry out the research work, a visit was made to the entity to learn about administrative management in the management of human resources, as well as to obtain general information about its organizational structure, the main activities it carries out and its managers. The design of the internal control manual for the cooperative contains accounting and administrative policies and procedures that guarantee an effective management of resources, which are reflected in flowcharts to facilitate their understanding and proper functioning, which allow to visualize unnecessary activities and verify whether The distribution of work is balanced according to the needs of the entity. The methodology used facilitated the collection of necessary, timely and fundamental information to achieve the proposed objectives. Finally, it is concluded that the lack of an internal control manual design has allowed managers, officials and employees not to have specific knowledge of their functions, procedures, lines of authority, and hierarchical levels existing in the cooperative, which influences the development of each of its activities and especially in the quality of service.